2020
DOI: 10.7554/elife.55159
|View full text |Cite
|
Sign up to set email alerts
|

Condensin I subunit Cap-G is essential for proper gene expression during the maturation of post-mitotic neurons

Abstract: Condensin complexes are essential for mitotic chromosome assembly and segregation during cell divisions, however, little is known about their functions in post-mitotic cells. Here we report a role for the condensin I subunit Cap-G in Drosophila neurons. We show that, despite not requiring condensin for mitotic chromosome compaction, post-mitotic neurons express Cap-G. Knockdown of Cap-G specifically in neurons (from their birth onwards) results in developmental arrest, behavioural defects, and dramatic gene ex… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 73 publications
1
8
0
Order By: Relevance
“…In almost all cases, these genes partially evaded the widespread transcriptional down-regulation that is inflicted by heat shock. A function in facilitating gene expression changes is consistent with the recently observed role of condensin in executing the transcriptional neuronal maturation programme in flies (Hassan et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…In almost all cases, these genes partially evaded the widespread transcriptional down-regulation that is inflicted by heat shock. A function in facilitating gene expression changes is consistent with the recently observed role of condensin in executing the transcriptional neuronal maturation programme in flies (Hassan et al, 2020).…”
Section: Discussionsupporting
confidence: 84%
“…Factors involved in the maintenance of neuronal transcriptomes during early neuronal maturation can have less severe phenotypes in fully differentiated neurons in which synapses have been formed (Southall et al , 2014 ; Hassan et al , 2020 ). This correlates with observed changes to the underlying chromatin landscape which is dynamic during differentiation and neuronal maturation (Marshall & Brand, 2017 ; Aughey et al , 2018 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that factors involved in the maintenance of neuronal transcriptomes during early neuronal maturation can have less severe phenotypes in fully differentiated neurons in which synapses have been formed (Hassan et al, 2020; Southall et al, 2014). This correlates with observed changes to the underlying chromatin landscape which is dynamic during differentiation and neuronal maturation (Aughey et al, 2018; Marshall and Brand, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…It is possible to speculate that Mi-2/dMEC is required to establish a stable epigenetic state following recruitment by sequence specific transcription factor binding, after which these states are maintained by separate chromatin modifying proteins or complexes. We previously observed that neuron-appropriate gene expression programmes were maintained by Cap-G, a member of the condensin complex (Hassan et al, 2020). Similarly, with Mi-2 knockdown, less severe phenotypes – and fewer misregulated genes were apparent upon Cap-G depletion, indicating that multiple factors may act to maintain the neuronal transcriptome in early neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%